Performance of broiler contract farmers: A case study in Perak, Malaysia - Majid, Rasak; Hassan, Sallahuddin (Elsevier B.V., 2014)
Contract broiler farming is one the system used to increase poultry production in Malaysia.Broiler contract farmers (BCF) participate in this system for having some benefits.This paper has evaluated economic performance of the BCFs in Perak.An economic evaluation of 60 BCFs was conducted in Perak to determine the performance of the system using economic performance analysis.Panel regression model was used in the analysis. This model involves price per bird (PRM) as dependent variable and size of farm (SOF), feed conversion rate (FCR), average body weight(ABW), average marketing age (AMA), mortality rate (MOR), and rearing housing system (DU).The results show that all variables, except SOF, are significantly influence the performance of BCF at five percent level of significance.